Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Join our platform to connect with experts ready to provide accurate answers to your questions in various fields. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.

-2x+6y=6 -7x-8y=-5 when using substution


Sagot :

we can simplify the first equation into
-x + 3y = 3
which can become
x = 3y - 3

we can then plug it into the second equation
-7(3y-3) - 8y = -5     [distribute]
-21y + 21 - 8y = -5   [now add like terms]
-29y = -26               [then divide both sides by -29]
y = 26/29               [then plug this into the first equation to get x]

x = 3(26/29) - 3 = 78/29 - 87/29
x = -9/29

therefore your answer is x = -9/29 and y = 26/29
or (-9/29 , 26/29)